Lessons from Uganda on Strategies to Fight Poverty - Mackinnon, John; Reinikka, Ritva (World Bank, Washington, DC, 2015)
Countries receiving debt relief under the Heavily Indebted Poor Countries initiative will be among the first to benefit from the new World Bank -- International Monetary Fund approach to strengthening the impact on poverty of concessional assistance in low-income countries. The new approach features a more inclusive and participatory process for helping recipient countries develop poverty reduction strategies. From these strategies, joint Poverty Reduction Strategy Papers (PRSPs) will bring together the country's own priorities and Bank-Fund assistance to the country. In Uganda, such a strategy has existed for several years. Uganda was one of the first low-income countries to prepare a comprehensive national strategy for poverty reduction using a participatory approach. Indeed, its experience contributed substantially to the design of the PRSPs. Uganda's top leadership is heavily committed to poverty reduction. Formulation of Uganda's Poverty Eradication Action Plan (PEAP) in 1996-97 was the executive branch's effort to make that commitment and vision operational. The authors draw lessons from the drafting of Uganda's PEAP. First, the plan made extensive use of existing data and research about Uganda to refocus a range of public policies and interventions relevant to poverty reduction. Second, the government's approach was highly participatory, with central and local governments, the donor community, nongovernmental organizations and civil society, and academics invited to contribute. Third, the government was quick to translate the plan into its budget and medium-term spending framework. Public expenditures on basic services were significantly increased after adoption of the PEAP in 1997. The authors discuss the general characteristics of a poverty reduction action plan, drawing on Uganda's experience; discuss what is known about poverty in Uganda and identify shortcomings in the data; examine the macroeconomic and fiscal policies that were considered most important to poverty reduction during the participatory process; discuss the delivery of public services, especially those that directly affect the poor; and highlight problems associated with land issues, including problems with access to credit and financial services and with the security of productive assets.